Teacher Recruitment and Selection Processes as A Leadership Challenge in Katsina State - Umar, Umar Abdulkadir; Adamu, Isyaku (Mahesa Research Center, 2025)
The challenges bedeviling the recruitment of teachers in Katsina State are increasingly raising concern among well-meaning citizens as well as leaders entrusted with the responsibility of recruiting qualified teachers. This paper aims to find out the challenges militating against teacher recruitment in Katsina state and solution pathways to the menace. The study aims to answer the question: What are the challenges militating against teacher recruitment in Katsina State? The study intended to use secondary sources of data in order to generate the facts regarding issues affecting teacher recruitment, as well as reviewing leaders’ lackadaisical attitudes in confronting the ever-growing challenges in Nigeria and Katsina state in particular. The paper discovered among the following, a lack of recruiting teachers with the required teaching qualifications, political interference in the recruitment process, corruption and bribery in the recruitment process, sectionalism and religious biases, a lack of attractive remuneration for teachers, lack of openness in the process. The paper recommended the following: recruitment of talented and qualified teachers, openness and transparency in the recruitment process, stick to merit in the recruitment process, details of the job description in the process, and due process in the screening of potential teachers.